2009
DOI: 10.1007/dcr.0b013e31819d47b5
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Assisted Laparoscopic vs. Open Subtotal Colectomy for Severe Ulcerative Colitis

Abstract: Although the operative time was elongated in the laparoscopic group, intraoperative safety and postoperative recovery were satisfactory. For severe ulcerative colitis, hand-assisted laparoscopic surgery can be an alternative to conventional open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 18 publications
4
51
1
Order By: Relevance
“…Several studies have reported the feasibility and safety of laparoscopic assisted total colectomy for ulcerative colitis in the elective setting, and shown the advantages of laparoscopic assisted total colectomy such as reduced postoperative pain, earlier return of intestinal function, decreased length of hospital stay, and improved cosmesis (Marcello et al, 2000;Hashimoto et al, 2001;Seshadri et al, 2001;Gill et al, 2004;Kienle et al, 2005;Larson et al, 2005). On the basis of these results, several studies have evaluated the feasibility and safety of minimally invasive surgery for selected patients with severe ulcerative colitis (Dunker et al, 2000;Bell & Seymour, 2002;Marceau et al, 2007;Fowkes et al, 2008;Watanabe et al, 2009;Holubar et al, 2009;Chung et al, 2009;Maggiori et al, 2010;Telem et al, 2010). These retrospective trials indicated that minimally invasive subtotal colectomy for selected patients with severe ulcerative colitis associated with a marked reduction in wound complication rate, time to return of bowel function, and mean hospital stay, although most of these studies have reported that the mean operating time was longer than open surgery.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have reported the feasibility and safety of laparoscopic assisted total colectomy for ulcerative colitis in the elective setting, and shown the advantages of laparoscopic assisted total colectomy such as reduced postoperative pain, earlier return of intestinal function, decreased length of hospital stay, and improved cosmesis (Marcello et al, 2000;Hashimoto et al, 2001;Seshadri et al, 2001;Gill et al, 2004;Kienle et al, 2005;Larson et al, 2005). On the basis of these results, several studies have evaluated the feasibility and safety of minimally invasive surgery for selected patients with severe ulcerative colitis (Dunker et al, 2000;Bell & Seymour, 2002;Marceau et al, 2007;Fowkes et al, 2008;Watanabe et al, 2009;Holubar et al, 2009;Chung et al, 2009;Maggiori et al, 2010;Telem et al, 2010). These retrospective trials indicated that minimally invasive subtotal colectomy for selected patients with severe ulcerative colitis associated with a marked reduction in wound complication rate, time to return of bowel function, and mean hospital stay, although most of these studies have reported that the mean operating time was longer than open surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Laparoscopic assisted surgery for severe ulcerative colitis is still technically difficult because of bowel friability and hypervascularity, creating a high likelihood of perforation and bleeding. A few recent studies assessed hand-assisted laparoscopic surgery for selected patients with severe ulcerative colitis (Watanabe et al, 2009;Holubar et al, 2009;Chung et al, 2009). The use of this technique may be adequate for severe ulcerative colitis because hand-assisted surgery enables surgeons to obtain tactile sensation, manual retraction, and digital vascular control, which could allow complex laparoscopic operations to be performed more effectively and satisfactorily.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HAL has rarely been highlighted as a separate procedure, and to the best of our knowledge, this is probably the only report focused on HAL emergency colectomy except for a report from Watanabe et al concerning HAL emergency subtotal colectomy for severe ulcerative colitis. 18 Despite the various advantages of HAL mentioned above, it also has a limitation. There still exist conversion cases; in our series, two patients were converted to open because of the cancer volume and infiltration to adjacent organ.…”
Section: Discussionmentioning
confidence: 99%